Pembuatan Motion Graphic untuk Memperkenalkan Perpustakaan kepada Siswa Sekolah Dasar dalam Bentuk Video - Nadia Marta Gusman; Marlini Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract In this paper we discuss "Motion Graphic Loading to Introduce Libraries to Elementary School Students". This paper aims to introduce libraries to elementary school students. The purpose of writing describes the making of motion graphics to introduce libraries to elementary school students. Writing this paper is done with 6 stages of making motion graphics. Based on the analysis of the data, it was concluded that the stages of making motion graphics are as follows. (1) concept, namely determining product specifications, namely title, duration, goals, objectives and final results; (2) design is the stage of making a graphic graphic specifically that is visualized through images; (3) collecting material is the stage of collecting materials according to what will be done; (4) assembly is the stage of making all objects by designing, animating and compositting; (5) the testing stage is the motion graphic testing stage that has been made; (6) distribution is the final stage of product packaging and distribution.Keywords: motion graphic, introducing the library